2004
DOI: 10.1080/0307945042000220714
|View full text |Cite
|
Sign up to set email alerts
|

A pathological condition possibly caused by spontaneous trichotecene poisoning in Brahma poultry: first report

Abstract: Trichotecene poisoning in poultry can cause oral lesions, haemorrhages, depletion and necrosis in the lymphopoetic organs and death. Spontaneous poisonings with these toxins are rarely described. This paper describes the spontaneous poisoning of two Brahma chickens with T-2 toxin, diacetoxyscirpenol and deoxynivalenol. Two out of 10 chickens died under signs of depression and loss of appetite. Histopathological analysis revealed vacuolar dystrophy of the liver, necrosis and depletion of lymphocyte in the bursa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Those samples derived from farms with evidenced poultry health problems with indications of possible trichothecene poisoning (Konjevic et al, 2004). Experimental toxicosis caused by trichothecene mycotoxins in poultry is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Those samples derived from farms with evidenced poultry health problems with indications of possible trichothecene poisoning (Konjevic et al, 2004). Experimental toxicosis caused by trichothecene mycotoxins in poultry is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…For gram negative bacteria, the endotoxin LPS is recognized by TLR2 and TLR4 [ 21 , 22 ]. LPS stimulation disrupts the histo-morphological organization of different organs including BF of chicken [ 23 , 24 ]. Reduced body and bursa weight are also characteristic of salmonella LPS stimulated chickens [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies DAS mainly affected blood parameters (leukopenia and/or anaemia), bone marrow, spleen, liver and testes. Konjevic et al (2004) condition. Sklan et al (2003) demonstrated that feeding DAS at concentrations of up to 1 mg/kg for more than 30 days influenced small intestinal morphology, but did not affect growth or antibody production in young poults.…”
Section: Chronic Toxicity Animalsmentioning
confidence: 99%